The Role of Artificial Intelligence in Law Enforcement: Towards a More Accurate and Efficient Justice System - Dachlan, Syahrir Nur; Karauwan, Donny Eddy Sam; Lahangatubun, Nurjana (Yayasan Sinergi Kawula Muda, 2024)
This research aims to examine the impact of the use of Artificial Intelligence (AI) in the criminal justice system in Indonesia on human rights and address the misuse of AI algorithms. The method used is normative legal research with secondary data analysis from literature study. The novelty of this research lies in its particular focus on the implications of AI use on human rights in criminal justice and mitigation strategies for algorithm misuse. The contribution of this research is to provide insight into the role of AI in law enforcement as well as regulative and practical recommendations. The results show that AI has great potential in improving the efficiency of the justice system, but also poses a risk of human rights violations if not properly regulated. Therefore, special regulations, transparency in the use of AI by law enforcement, and public education are needed to ensure fairness and safety in its use